Adaptogenic properties of the Lady’s Mantle (Alchemilla vulgaris L.) (literature review) - N. A. Palchikova; V. G. Selyatitskaya; M. I. Voevoda (Сибирский научный медицинский журнал, 2024)
Adaptogens are a category of herbal medicinal products that enhance the adaptive reserves of the body, resistance to extreme factors and survival under stress. Adaptogenic properties have been revealed in dozens of plants, in particular, preparations based on raw materials from the Lady’s Mantle (Alchemilla vulgaris L.), a perennial herbaceous plant from the family Rosaceae, have a wide range of biological activity, including antioxidant, antiinflammatory, neuroprotective, anticancer and other, which allows them to be used for prevention and supportive therapy in the treatment of many pathological processes. The results of the authors’ own research and a number of literature data substantiate the presence of adaptogenic properties in this plant. The review analyzes the information in the scientific literature on the chemical composition of compounds included in preparations based on A. vulgaris raw materials, the modern interpretation of the concept of “adaptogen” and criteria for evaluating the adaptogenic properties of plants, and discusses possible molecular and cellular mechanisms that ensure the presence of such properties in the Lady’s Mantle.